Tapada da Ajuda (Lisbon, Portugal) Bronze Age pin - Melo, Ana Ávila de (2019)
A pin made of a copper-based alloy, found at Tapada da Ajuda (Lisbon, Portugal), a site dated to the beginning of the Late Bronze Age, was analyzed by X-ray fluorescence (XRF) spectroscopy and examined by microscopy. The results of this study and the unusual manufacturing technique of the pin are presented and discussed in this paper. Typology and production technique of this object seem to indicate a Central European origin.